STUDI SIMULASI NUMERIK PENGARUH PENAMBAHAN FINS SETENGAH SILINDER DISUSUN SECARA STAGGERED TERHADAP KINERJA KOLEKTOR SURYA PEMANAS UDARA DENGAN PLAT PENYERAP V-CORRUGATED - Sulaiman Ali; Djatmiko Ichsani (Program Studi Teknik Mesin Universitas Tarumanagara, 2018)
Abstract: The use of solar energy by using solar collector has been extensively researched to optimize existing solar energy source, one of the methods to utilize solar energy is by using solar collector and has been widely utilized by humans in the drying process. To create a solar collector with optimum performance the thermal efficiency needs to be increased, as for increasing the thermal efficiency of solar collector one by extending the absorption field and increasing the convection heat transfer coefficient by creating a turbulent flow inside the solar collector duct, the flow turbulence can be achieved by Provides obstacle and fins disturbance to the flow direction of the working fluid under the hot absorber plate. This research was conducted with 3D Steady flow numerical simulation with turbulence viscos k-omega SST. The objective of this research is to know the optimum diameter and spacing of fins variation with 6mm, 8mm, and 10mm fins diameter, and variation of fins distance to obstacle 0,25L; 0.5L and 0.75L. The result of numerical simulation optimum fins is determined by the smallest ratio of ΔP/ΔT and this research continued to the experiment. The solar collector used in this study is a solar collector using a v-corrugated absorber plate with triangular obstacle and half cylindrical fins arranged staggered inside a solar collector duct. The results obtained from this research is, the most optimum half cylinder fins are 6 mm fins with a fins distance to obstacle 0.75L.